The Effectiveness of the Blended Education Strategy in Learning the Skills of Rolling and Suppression Football for Students - Abbas Abdulhamza Kadhem; Khalil Hamid Mohammed Ali; Ahmed Sekeb Gaeed (Institute of Medico-legal Publications Pvt Ltd, 2021)
The world has witnessed a development in all areas of the educational process and physical education is one of these areas and the fact of its effect on the body has been based on different sciences, whether in terms of physical-skills-health-psychological, to reach the high level of performance, hence the importance of research in The use of educational units based on the blended learning strategy to learn the technical performance of my skills (rolling, Suppression) in football, using the scientific foundations and good investment of the content of the material concerned with the study.The research aims to, identify the effect of blended education strategy on learning to perform the skills of rolling and Suppression football. To achieve this goal, the researcher used the experimental method by designing the two equal groups, and the research community was determined by the students of the first stage of the College of Physical Education and Sports Sciences - Karbala University for the 2017-2018 academic year and their number (141 / students). The researcher chose a lottery (30 / students) by (15 students) for each group of the two research groups (experimental and control).And after processing the data statistically, the researcher reached several conclusions ,the two research groups achieved an improvement in the study variables, but with varying proportions, and the results indicated the superiority of the members of the experimental group that used the mixed education strategy in comparison with the method used in the studied variables.